Study Noise Effects on The Students of The Faculty of Engineering/ Mustansiriyah University - Ibrahim, Shatha Abduljabbar (Al-Nahrain Journal for Engineering Sciences, 2018)
Noise effects on the students include both auditory and non-auditory effects and cause ?the lack of concentration and disability of learning? ?and communication. The Faculty of ?Engineering was chosen to conduct the questionnaire ?because the students have both ?theoretical and practical courses and they ?spend one-third of their day in the ?laboratories, so it is expected they exposure to noise more than other faculties’ students ?A questionnaire was conducted to understand the effect of noise on student behavior ?and whether they could classify the sounds that they heard as noise and determine the ?noise sources (indoor, outdoor) and the noisiest places (classroom, laboratory, and ?campus). 438 students participated in this questionnaire from all stages, and they ?covered eight engineering departments in the Faculty of Engineering, Mustansiriyah ?University. A statistical analysis of the questionnaire found that 39.5%, 46%, 32% and ??49% of students suffered from noise in classrooms, laboratories, open spaces and closed ?spaces (campus), respectively. In the actual situation, the effects that students ?experience can be arranged in the following descending order: feeling discomfort, ?hearing difficulty, raising the voice when speaking, lack of concentration, headache, ?tinnitus and nausea. Using a sound and vibration meter with the analyzer, the noise ?levels in dBA were measured in the noisiest places that the students mentioned. The ?noise levels exceed the standard limitation that organizations and agencies such as the ?WHO determined. ??